Biomechanical Properties of 3D-Printed Cervical Interbody Fusion Cage With Novel SF/nHAp Composites - Chen, Shuang; Meng, Yi; Wu, Guozhi; Liu, Zhize; Lian, Xiaodong; Hu, Jianyu; Yang, Dongfang; Zhang, Guiqi; Li, Kun; Zhang, Hao (Frontiers in Materials, 2021)
Anterior cervical discectomy and fusion (ACDF) is a commonly used surgical method for the treatment of cervical spondylosis. As the ACDF surgery is widely used in clinics, how to use suit-able materials to design and prepare cervical interbody fusion cages is a hot research topic. Here, we describe a new three-dimensional (3D) printing approach to create stretchable and tough silk fibroin/nano-hydroxyapatite (SF/nHAp) composites with tunable mechanical properties. The com-pressive strength of the novel composites with biomimetic structure could reach more than 128 MPa. More importantly, the composites were prepared by 30% silk fibroin and 70% hydroxyap-atite, which was very similar to the human bone tissue. Finite element analysis results indicate that the stress distribution of SF/nHAp composites cervical interbody fusion cage in vivo is more uni-form than that of commercial Ti alloy cages. This study provides the effectiveness of SF/nHAp composite to apply in cervical interbody fusion cages interbody fusion cage and in the field of bone tissue engineering.